Reproductive intentions and corresponding use of safer conception methods and contraception among Ugandan HIV clients in serodiscordant relationships - Glenn J. Wagner; Deborah Mindry; Emily A. Hurley; Jolly Beyeza-Kashesya; Violet Gwokyalya; Sarah Finocchario-Kessler; Rhoda K. Wanyenze; Mastula Nanfuka; Mahlet G. Tebeka; Kathy Goggin (BMC, 2021)
Abstract Context Among people living with HIV in Uganda, desires to have a child and unplanned pregnancies are both common, while utilization of safer conception methods (SCM) and modern contraceptives are low. Methods Three hundred eighty-nine HIV clients who reported considering childbearing with their uninfected partner enrolled in a safer conception counseling intervention trial in Uganda. Multiple regression analysis and baseline data were used to examine correlates of reproductive intentions and behaviors, including use of safer conception methods and contraception. Results Most (n = 313; 80.5%) reported that both they and their partner wanted to have a child now, which was associated with being married, in a longer relationship, not having a child with partner, greater SCM knowledge, lower internalized childbearing stigma, and higher perceived community stigma of childbearing. However, just 117 reported trying to conceive in the prior 6 months, which was associated with being female, not having a child with their partner, less decision-making control within the relationship, and greater perceived cultural acceptability of SCM. Among those who had tried to conceive in the past 6 months, 14 (11.9%) used SCM, which was associated with greater control in decision making. Of the 268 who were not trying to conceive, 69 (25.7%) were using a modern contraceptive, which was associated with being in a shorter relationship, less control over decision-making, more positive attitudes towards contraception and lower depression. Conclusion Methods to promote reproductive goals are underused by HIV serodiscordant couples, and relationships characteristics and childbearing-related stigma appear to be most influential and thus targets for intervention. Trial registration Clinicaltrials.gov, NCT03167879 ; date registered May 23, 2017.